2022
DOI: 10.1371/journal.pone.0268660
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the genome and silk-gland transcriptomes of Darwin’s bark spider (Caerostris darwini)

Abstract: Natural silks crafted by spiders comprise some of the most versatile materials known. Artificial silks–based on the sequences of their natural brethren–replicate some desirable biophysical properties and are increasingly utilized in commercial and medical applications today. To characterize the repertoire of protein sequences giving silks their biophysical properties and to determine the set of expressed genes across each unique silk gland contributing to the formation of natural silks, we report here draft ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Moreover, spiders are important model for evolution and adaptive radiation given the varied environmental conditions of their habitats 3 . Taking advantage of the ever expanding genomic information, researchers are able to untangle different aspects of spider biology, with particular interest on venom, silk, and the phylogeny 4 17 . The increasing numbers of genomes will facilitate the phylogenomic study to unravel the roots of spiders and comparative studies to decipher the morphological and behavioural traits of spiders.…”
Section: Background and Summarymentioning
confidence: 99%
“…Moreover, spiders are important model for evolution and adaptive radiation given the varied environmental conditions of their habitats 3 . Taking advantage of the ever expanding genomic information, researchers are able to untangle different aspects of spider biology, with particular interest on venom, silk, and the phylogeny 4 17 . The increasing numbers of genomes will facilitate the phylogenomic study to unravel the roots of spiders and comparative studies to decipher the morphological and behavioural traits of spiders.…”
Section: Background and Summarymentioning
confidence: 99%
“…Furthermore, arachnids are prolific producers of biomaterials most notable among which are venoms and silks (Foelix, 2011). The variety of such biomaterials (Sethy and Ahi, 2022), and their genetic underpinnings (Arakawa et al, 2022;Babb et al, 2022)-most of which remain largely unknown (e.g. we know only a handful of the likely hundreds of thousands of silk types produced by tens of thousands of species)represent underappreciated dimensions of biodiversity.…”
Section: Grand Challenge 1 Assess Arachnid Species Richness For Compa...mentioning
confidence: 99%
“…Evidence has been found for ancient lateral gene transfer events to arachnids from bacteria or fungi (Dong et al, 2018). Genomic and transcriptomic studies have so far focused on annotating gene families that encode for morphological development (Hoy et al, 2016;Zhang et al, 2019;Harper et al, 2021), for venom neurotoxins (Cao et al, 2013;Yu et al, 2019), for silks (Babb et al, 2017;Garb et al, 2019;Kono et al, 2021;Babb et al, 2022), for dietary characteristics (Grbicé t al., 2011;Hoy et al, 2016;Fan et al, 2021), for enzymes that cause allergies in vertebrates (Dong et al, 2018), for candidate genes for sex determination (Hoy et al, 2016;Miller et al, 2022), and for genes important for the innate immune system (Shingate et al, 2020). Large scale comparative genomics has also started to understand the genetic basis for tick-borne diseases (Jia et al, 2020).…”
Section: Grand Challenge 3: Interpret Arachnid Trait Evolution Throug...mentioning
confidence: 99%
“…Babb et al (2017) annotated 28 spidroin genes in Trichonephila clavipes and found their expression in several silk glands to be complex, as well as sex-specific (Correa-Garhwal et al, 2021). The genomes and transcriptomes of bark spiders (genus Caerostris) reveal a repertoire of no fewer than 31 spidroins (Garb et al, 2019;Kono et al, 2021;Babb et al, 2022). In comparison, studies of the genomes of other spiders have annotated fewer spidroins: 11 in Araneus ventricosus (Kono et al, 2019), 10 in Uloborus diversus (Miller et al, 2022), 16 in a non-web-building wolf spider (Yu et al, 2019).…”
Section: Grand Challenge 3: Interpret Arachnid Trait Evolution Throug...mentioning
confidence: 99%